2016
DOI: 10.1038/srep23860
|View full text |Cite
|
Sign up to set email alerts
|

Using the incidence and impact of behavioural conditions in guide dogs to investigate patterns in undesirable behaviour in dogs

Abstract: The domestic dog is one of our most popular companions and longest relationships, occupying different roles, from pet to working guide dog for the blind. As dogs age different behavioural issues occur and in some cases dogs may be relinquished or removed from their working service. Here we analyse a dataset on working guide dogs that were removed from their service between 1994 and 2013. We use the withdrawal reasons as a proxy for the manifestation of undesirable behaviour. More than 7,500 dogs were in the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Hence, in addition to welfare concerns arising from exposing working dogs to fear-provoking situations for which they are poorly prepared, and the issue of handler safety when dogs perform poorly, there are potential economic consequences. Fear and anxiety can lead to the loss of dogs from programs at assessment, during training, or later through early withdrawal from active working roles (Caron-Lormier et al, 2016), with an associated loss of the potential contribution they could make during their working lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in addition to welfare concerns arising from exposing working dogs to fear-provoking situations for which they are poorly prepared, and the issue of handler safety when dogs perform poorly, there are potential economic consequences. Fear and anxiety can lead to the loss of dogs from programs at assessment, during training, or later through early withdrawal from active working roles (Caron-Lormier et al, 2016), with an associated loss of the potential contribution they could make during their working lives.…”
Section: Introductionmentioning
confidence: 99%
“…Goddard and Beilharz, 1982; 1984a,b), influences of the environment (Lefebvre et al, 2007), and learned experiences during particular sensitive periods (Appleby et al, 2002) and throughout life. Fear-related behavior compromises performance, leads to significant numbers of dogs failing to complete training (e.g., Murphy, 1995;Batt et al, 2008), early withdrawals from working roles (Caron-Lormier et al, 2016), and can jeopardize dog and handler safety. Hence, amelioration of fear and anxiety is critical to maintain dogs in working roles and to ensure their well-being.…”
mentioning
confidence: 99%
“…In our previous works Caron-Lormier and colleagues used a historic dataset to understand both the incidence and impact of health and behavioural issues in working guide dogs, in terms of reduced days of working life [17, 18]. These studies give a good description of the situation, integrating incidence and impact information to reveal which disorders had the most overall impact on the population.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the effect of undesirable behaviour on withdrawal of working guide dogs, we reported that the issues affecting the greatest number of guide dog partnerships were environmental anxiety, training related breakdowns, and fear/aggression [18]. However, the issues that led to the greatest reduction in working life were fear/aggression, chasing, and attentiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation